2021
DOI: 10.1016/j.afos.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sarcopenic obesity in community-dwelling healthy Indian adults - The Sarcopenic Obesity-Chandigarh Urban Bone Epidemiological Study (SO-CUBES)

Abstract: Objectives To determine the prevalence of sarcopenia obesity (SO) in healthy Indian adults and delineate the relative impact of the 3 indices of obesity [body mass index (BMI), waist circumference (WC), fat mass percent (FM%)] with regards to inter-definitional agreement and their relationship with usual gait speed (GS). Methods Apparently healthy adults (aged ≥ 20 years) with no background history of comorbidities were enrolled from the community by door-to-door survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Those with high BMI may therefore be less likely to have concomitant sarcopenia as opposed to when obesity is defined by body fat percentage [ 28 , 29 ]. In a study of 804 community-dwelling healthy Indian adults, body fat percentage was reported to be a better diagnostic criterion for sarcopenic obesity as it assesses body fat distribution unlike other methods such as by BMI or waist circumference [ 10 ]. Although consensus definitions of sarcopenic obesity are not currently available, it would appear that the obesity component should be defined where possible using direct estimates of adiposity such as by DXA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those with high BMI may therefore be less likely to have concomitant sarcopenia as opposed to when obesity is defined by body fat percentage [ 28 , 29 ]. In a study of 804 community-dwelling healthy Indian adults, body fat percentage was reported to be a better diagnostic criterion for sarcopenic obesity as it assesses body fat distribution unlike other methods such as by BMI or waist circumference [ 10 ]. Although consensus definitions of sarcopenic obesity are not currently available, it would appear that the obesity component should be defined where possible using direct estimates of adiposity such as by DXA.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is another age-associated condition and is defined as the loss of skeletal muscle mass and function which increases the risk of adverse musculoskeletal outcomes [ 7 10 ]. The prevalence of sarcopenia for those aged > 45 years is between 5 and 39%, depending on the definition of sarcopenia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A German study [ 36 ] in women over 70 years using the EWGSOP-1 definition of sarcopenia found a prevalence of sarcopenic obesity of 0% when obesity was diagnosed by BMI and of 2.3% with the percentage of fat criterion. A recent Indian study [ 37 ] applying the EWGSOP-2 definition of sarcopenia has reported a prevalence of sarcopenic obesity in the over-65 population of 3.8% in women and 6.7% in men when obesity was diagnosed by BMI, and 5.7% in women and 6.7% in men when diagnosed by fat percentage. The data reported in both studies are fairly similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…A global study reported sarcopenia prevalence of 17.5% in Indian elderly (≥ 65 years) [ 1 ]. Indian studies have reported a prevalence of 14.2% (≥ 60 years) from South India [ 6 ] and 3.2% in community dwelling North Indians (≥ 20 years; younger population in SO-CUBES study) [ 7 ]. According to the SARIR Study from Iran the prevalence of presarcopenia (52.7% vs 25.3%), sarcopenia (20.7% vs 15.3%), and severe sarcopenia (6% vs 5.3%), were higher in men than women (> 55 years) [ 8 ].…”
Section: Epidemiologymentioning
confidence: 99%